Leveraging Artificial Intelligence (AI) to Enhance Learning Motivation Among Educational Technology Students at UNESA Campus 5 Magetan in the Digital Era - Riski Dwi Andrian; Hilmawan Wibawanto (Journal on Smart Learning Technologies, 2026)
The rapid development of Artificial Intelligence (AI) has brought significant changes to the learning process in higher education, particularly in enhancing students' learning motivation. This study aims to analyze the level of AI utilization in students’ learning activities and its influence on learning motivation and critical thinking skills. The study employed a quantitative approach with a descriptive-exploratory design supported by simple qualitative data. Data were collected through Likert-scale questionnaires and open-ended questions from students of the Educational Technology Study Program at Universitas Negeri Surabaya Magetan Campus 5. The results showed that AI utilization is in the high category and has become an integral part of students’ learning process. AI serves as a reference source, a tool to understand complex materials, and a support for task completion, thereby increasing learning effectiveness and efficiency. The use of AI also proved to enhance students’ learning motivation, activeness, and self-confidence. However, a tendency of over-reliance on AI was found, which has the potential to reduce critical thinking skills due to the cognitive offloading phenomenon. The study concludes that AI has an ambivalent role as both a supporter and a potential risk in learning. Therefore, the utilization of AI must be balanced with critical AI literacy and appropriate pedagogical strategies so that the technology functions as a supporter of the thinking process rather than a substitute.